Conservative Features in Latin American Models of Radical Change. An Interpretative Essay on the Roots of Populism - Mansilla, H. C. F. (Nómadas. Critical Journal of Social and Juridical Science, 2013)
Actual populist regimes (like those in Bolivia, Ecuador, Nicaragua, and Venezuela) disseminate an ideology of radical change, but in many aspects they reproduce authoritarian and premodern elements of the ancient indigenous civilizations and of the Spanish colonial time. The result is the repetition of old conventions: the consolidation of the political culture of authoritarianism, the formation of very privileged elites (which build now the upper classes), and the desinstitutionalization of public and political life.